Wortsprachliche Merkmale im Alemannischen - Caro Reina, Javier (Linguistik Online, 2019)
This paper examines the strategies for profiling the phonological word in Alemannic, applying the typology of syllable and word languages. The diagnostic criteria selected for assessing the relevance of the phonological word include syllable structure, phonotactic restrictions, and word-profiling processes. Following on from previous synchronic and diachronic analyses (Nübling/Schrambke 2004; Szczepaniak 2007), I will provide a detailed account of the phonological word in Old Alemannic and in modern Alemannic dialects, which include Upper-Rhine Alemannic, Swabian, and South Alemannic. It will be shown that the relevance of the phonological word gradually increased in Alemannic, as can be gleaned from processes such as unstressed vowel reduction, unstressed vowel deletion, and consonant epenthesis. While vowel reduction created strong asymmetries between stressed and unstressed syllables, unstressed vowel deletion and consonant epenthesis increased syllable complexity at word and morpheme boundaries. In addition, Swabian was found to contain more word-related features than Upper-Rhine Alemannic and South Alemannic. Thus, the typology of syllable and word languages contributes to a better understanding of language variation and change in Alemannic.